2021
DOI: 10.1016/j.omto.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of non-viral, ligand-dependent, EPHB4-specific chimeric antigen receptor T cells for treatment of rhabdomyosarcoma

Abstract: Ephrin type-B receptor 4 (EPHB4), expressed in tumors including rhabdomyosarcoma, is a suitable target for chimeric antigen receptor (CAR)-T cells. Ligand-independent activation of EPHB4 causes cell proliferation and malignant transformation in rhabdomyosarcoma, whereas ligand-dependent stimulation of EPHB4 induces apoptosis in rhabdomyosarcoma. Therefore, we hypothesized that ligand-based, EPHB4-specific CAR-T cells may kill rhabdomyosarcoma cells without stimulating downstream cell proliferation mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…As previously reported, the EPHB4‐CAR‐T cells exhibited strong and durable potency against EPHB4 + RH30 cells, as demonstrated via xCELLigence ® Real‐Time Cell Analysis (Figure 3b). 7 These data were consistent with our previous data; therefore, we used these cells for conducting further NHP studies.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…As previously reported, the EPHB4‐CAR‐T cells exhibited strong and durable potency against EPHB4 + RH30 cells, as demonstrated via xCELLigence ® Real‐Time Cell Analysis (Figure 3b). 7 These data were consistent with our previous data; therefore, we used these cells for conducting further NHP studies.…”
Section: Resultssupporting
confidence: 91%
“…As this tendency was observed in the male macaque of the No Tx group and not observed in the male macaque of the CAR‐T group, it was considered an effect of the conditioning regimen. However, our previous study has revealed that EPHB4 is weakly expressed in renal tissue, 7 indicating the occurrence of possible renal toxicity. Nevertheless, the elevated BUN levels eventually returned to baseline levels; however, creatinine levels were not affected by the EPHB4‐CAR‐T cell infusion (Figure 2b).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations